Converting non-Mesogenic to Mesogenic Stacking of Amino-s-Triazine-Based Dendrons with p-CN Phenyl Unit by Eliminating Peripheral Dipole - Yao-Chih Lu; Yu-Tsz Hsu; Tsung-Yen Yang; I-Chun Liou; Sheng-Wei Wang; Po-Chia Huang; Jey-Jau Lee; Long-Li Lai; Hsiu-Fu Hsu (Nanomaterials, 2022)
Three new amino-s-triazine-based dendrons, 1a, 1b, and 1c, containing an aryl-CN moiety in the dendritic skeleton were prepared in 72–81% yields (1a: R1 = − N(n-C8H17)2, R2 = n-OC8H17, 1b: R1 = R2 = − N(n-C8H17)2, 1c: R1 = − N(n-C8H17)2, R2 = − N(n-C4H9)2). Dendrons 1a with N(n-C8H17)2 and n-OC8H17 peripheral substituents, surprisingly, did not show any mesogenic phase during the thermal process. However, non-mesogenic 1a can be converted to mesogenic 1b or 1c by eliminating the peripheral dipole arising from the alkoxy substituent; dendron 1b only comprising the same N(n-C8H17)2 peripheral groups showed a ~25 °C mesogenic range on heating and ~108 °C mesogenic range on cooling. In contrast, dendron 1c possessing different N(n-CmH2m+1)2 (m = 8 versus m = 4) peripheral units, having similar stacking as 1b, exhibited a columnar phase on thermal treatment, but its mesogenic range (~9 and ~66 °C on heating and cooling, respectively) was much narrower than that of 1b, attributed to 1c’s less flexible alkyl chains in the peripheral part of dendron. Dendron 1a with the alkoxy substituent in the peripheral skeleton, creating additional dipole correspondingly, thus, leads to the dendritic molecules having a non-mesogenic stacking. Without the peripheral dipole for intermolecular side-by-side interaction, dendrons 1b and 1c exhibit a columnar phase on thermal treatment because of the vibration from the peripheral alkyl chain.